Metamaterial engineered C+L band 90º hybrid with 150 nm feature size - Hadij-El-Houati, Abdelfettah; Halir, Robert; Ortega-Moñux, Alejandro; Wanguemert-Pérez, Juan Gonzalo; Podmore, Hugh; Schmid, Jens H.; Cheben, Pavel; Molina-Fernández, Íñigo (My University, 2020)
90º hybrids are important components for coherent optical communications. Conventional implementations only cover the C band, while broadband, metamaterial-based devices require sub-100nm feature sizes. We propose a design based on dual-etch silicon subwavelength structures that achieves a 170 nm bandwidth with deep-UV compatible feature sizes.
Keywords: Metamateriales; Silicio sobre aislante; MMI; Silicon on Insulator; 90º hybrid; coherent receiver; metamaterial; subwavelength grating